Social Networking Among Japanese Elders - Kawakami, Atsuko; Lehman, Derek; Burress, Kaitlynn (Advances in Social Sciences Research Journal, 2021)
The purpose of this study is to identify some of the predictors of social network formation with a focus on everyday behaviors such as greeting neighbors, attitudes about elder care, civic involvement, and hobby or social group membership. Using data from the 2010 and 2012 waves of the Japanese General Social Survey, we found that factors in which individuals have more control over are associated with the formation of social networks whereas factors that individuals have little to no control over are less likely to affect network formation. Specifically, elderly individuals who greet their neighbors and those who view elder care as an individual’s or family’s responsibility are more likely to have larger social networks. Likewise, civic engagement and participation in neighborhood associations are also significantly associated with forming social networks. Surprisingly, our analysis revealed that participating in hobby groups, length of residency in a community, and other control variables such as gender, income, and education are not significantly associated with forming social networks. Our findings indicate that the key components to building strong social networks are found within mundane daily activities. We conclude with several suggestions for how the elderly and communities can build elders’ social networks and thereby improve well-being. The implications of this study include raising awareness among individuals to prepare for a better, well-connected life in old age as well as suggesting local government programs for elderly care to help build more effective programs. Counselors could use this information to encourage their elderly clients to build social networks by increasing daily social interactions with neighbors and obtaining the view of self-reliance on elder care responsibility. Future researchers should seek to integrate the elder’s medical information in analyses in order to consider a comprehensive plan for the elderly’s well-being.